Legal Classification of Employment Relations of State Bureau of Investigation Personnel - D. Ye. Zherebtsov (Bulletin of Kharkiv National University of Internal Affairs)
The sectoral affiliation of employment relations concerning personnel of the State Bureau of Investigation (SBI) is examined. The scholarly contributions regarding the classification of service relations within law enforcement agencies are analyzed. Particular attention is given to the labor law status of various categories of SBI employees.